Laparoscopic radical gastrectomy for gastric cancer: an anatomical approach to right mesogastrium excision and its clinical significance - Pan, Guofeng; Guo, Zhixing; Huang, Likui; Zhang, Weihong; Li, Suping; Chen, Jian; Wu, Jihuang; Weng, Jianbin; Zhu, Zipeng; Lin, Jianjin; Li, Junpeng; Xu, Yanchang (Frontiers in Oncology, 2025)
ObjectiveRadical gastrectomy for gastric cancer involves the en-bloc resection of the primary tumor and complete excision of the mesogastrium. However, the surgical boundaries and techniques for removing lymph nodes above the pylorus during gastric cancer surgery remain unclear. We aimed to investigate a novel, standardized approach for excising the right mesogastrium in gastric cancer patients undergoing suprapyloric lymphadenectomy, focusing on surgical techniques and outcomes.MethodsOur surgical technique includes identifying three key elements of the mesogastrium: the encircling portion, the suspension point, and the connecting segment. Using these anatomical landmarks, we resect adipose tissue containing lymph nodes from the right mesogastrium and perform root ligation of the right gastric vessels. We then perform D2 lymphadenectomy combined with complete mesogastrium excision (D2+CME). We retrospectively analyzed clinical data from 376 patients who underwent laparoscopic radical gastrectomy with lymph node dissection for gastric cancer, comparing outcomes between laparoscopic suprapyloric lymph node dissection guided by mesogastric anatomy and traditional methods.ResultsA total of 376 patients were included, with 166 undergoing laparoscopic radical gastrectomy with D2+CME and 210 receiving traditional laparoscopic D2 gastrectomy. No significant differences were observed between the groups in age, body mass index, comorbidities, ASA score, tumor differentiation, tumor location, or surgical approach (P>0.05). The D2+CME group harvested significantly more lymph nodes than the traditional D2 group (43.84 ± 5.01 vs. 33.18 ± 2.96, P<0.001). The number of positive lymph nodes was also higher in the D2+CME group (6.12 ± 0.89 vs. 2.86 ± 0.55, P<0.001). The number of lymph nodes harvested from the right mesogastrium was greater in the D2+CME group (3.41 ± 0.48 vs. 1.32 ± 0.37, P<0.001). Intraoperative blood loss was lower in the D2+CME group (5.67 ± 0.41 vs. 9.96 ± 0.77, P<0.001), and dissection time was shorter (27.22 ± 1.50 vs. 31.31 ± 1.53, P<0.001). No significant difference was found in the number of positive lymph nodes in the right mesogastrium (P>0.05).ConclusionD2+CME is a feasible and effective approach for laparoscopic radical gastrectomy for gastric cancer. The mesogastric anatomical-guided method for suprapyloric lymph node dissection is safe, reliable, and improves lymph node dissection quality while reducing operative time.